The Strategic Role of Information Systems in Advancing Sustainable Business Practices - Puspitasari, Devi (Indonesian Scientific Publication, 2024)
Information systems are increasingly recognized as enablers of sustainable business practices. However, the extent of their impact across environmental, social, and governance (ESG) dimensions remains limited in current scholarship, particularly regarding mechanisms of influence. This narrative review investigates how information systems contribute to sustainability by enhancing operational efficiency, informing strategic decisions, and overcoming implementation challenges. Drawing from Scopus and Google Scholar, a systematic search was conducted using Boolean keyword combinations such as